Individual and partnership characteristics associated with consistent condom use in a cohort of cisgender men who have sex with men and transgender women in Nigeria - Oluwasolape Olawore; Trevor A. Crowell; Sosthenes C. Ketende; Habib O. Ramadhani; Hongjie Liu; Julie A. Ake; Afoke Kokogho; Sylvia Adebajo; Man E. Charurat; Rebecca G. Nowak; Stefan D. Baral; on behalf of the TRUST/RV368 Study Group (BMC, 2021)
Abstract Background This study reports on the individual and partnership characteristics that influence consistent condom use in cisgender men who have sex with men (MSM) and transgender women (TGW) attending trusted community centers that provide HIV prevention and treatment services in Nigeria. Methods Adults assigned male at birth who reported anal sex with male partners who enrolled between March 2013-2019 and had information about at least one male sexual partner were included in these analyses. At enrollment and follow-up visits every 3 months for up to 18 months, participants were administered detailed questionnaires that collected information about demographics, sexual practices, HIV risk behaviors, and characteristics and behaviors of their partners in the previous year (at enrollment) or the preceding 3 to 6-months (at follow-up visits). Logistic regression models with generalized estimating equations were used to assess the odds ratio (OR) and 95% confidence intervals (CI) of individual, partner, and partnership characteristics associated with consistent condom use (CCU). A participant was defined as consistently using condom if they reported always using condoms all the time they had insertive, receptive or both types of anal sex with a male partner. Results At the individual level, CCU was positively associated with higher education, disclosure of key population status to a healthcare worker and negatively associated with poor access to condoms. At the partner and partnership level, CCU was associated with partners with higher education (aOR: 1.36; 95% CI: 1.07-1.72), casual relationships (aOR: 1.22; 95% CI: 1.11-1.34) and relationships in which partners encouraged the participant to use condoms with other partners (aOR: 1.14; 95% CI: 1.02-1.28). Relationships in which the partner was married to a woman and/or the partner's HIV status positive or unknown were negatively associated with CCU. Conclusions These findings suggest that individuals in relationships where partners were more open and encouraged safer sex were more likely to consistently use condoms. HIV prevention programs should consider leveraging communication to sexual partners to encourage condom use as this may support condom use with other sexual partners. Given sustained and growing HIV and STI epidemics among MSM and TGW, even with pre-exposure prophylaxis scale-up, it is crucial to continue to study optimal implementation strategies to increase condom use.